(3ELGRI eMeO GHf fGUQ GdMGReis - (3eMeO Hf fGUQ GdMGRejs ((3eMeO Hf CMeO GdJhfci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi hab WGFaI ef GdYdeGA ai cd YUQ GdbjGe HCYHGA GdSfI GdeMeOjI Ydi GdJMbjb hNUge HeYQaI GdGSfGO aaGbhG Ydi ef ShGge hHYO ajbhd MSjf Hf eMSf GdGfUGQi GdNRQLi GdSYOi s
(3BNQgG (B:s
(3hfXQ Edi QhGjJg ai GdJaSjQ GdPi dg aai JfXjQg fXQkG hGQGO GdSeGY CQOJ GdJfHjg Ydi Pdc GfJgi eG hLOJg ef KHJ GdbGVi GdYdGeI CMeO Hf eMeO bGWf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdSYjOjI GdYGeI ` Jhfc (B((3GUhd MOjK (B39) s
Keywords: (3GdMOjK h GdeUWdMs